Application of a Rapid Micro-calorimetry Coupling Method in Quality and Integrity Control of Probiotic-Based Products - Hary Razafindralambo (New Visions in Science and Technology Vol. 2, 2021)
The objective was to apply a rapid and reliable method in quality and integrity control of probiotic-based products. For this purpose, various food grade ingredients and supplements, in pure or formulated forms, from European and American manufacturers, distributors, universities, and institutions coordinating microorganism collections have been analyzed. The method is based on the thermal profiling and fingerprinting of powder samples, using a coupling thermogravimetry - differential scanning calorimetry technique (TGA-DSC) under well-defined conditions. More than 100 monostrain and multistrain probiotics have been tested with this method, and each sample has shown a unique qualitative profile and significant different quantitative thermophysical data. This approach reveals not only the probiotic strain features but also those of molecular functional ingredients (e.g. cryoprotectors, antioxidants, etc.) added into the formulation (fingerprints, purity, water and volatile content, mineral compound amount, etc.). Moreover, the method is highly reproducible, sensitive, and adaptable to a high throughput analysis while requiring a small amount of sample. Besides the pure analytical aspects, it can also provide some relevant fundamental information such as the probiotic strain and product formulation thermostability.